2004
DOI: 10.1039/b400248b
|View full text |Cite
|
Sign up to set email alerts
|

Thorpe–Ingold effects in cyclizations to five-membered and six-membered rings containing planar segments. The rearrangement of N(1)-alkyl-substituted dihydroorotic acids to hydantoinacetic acids in base

Abstract: While the gem-dimethyl effect (GDME) is quantitatively similar for cyclizations to cyclopentane and cyclohexane rings and their homomorphs, in systems containing planar segments the GDME is stronger for the formation of five-membered rings. Planar pentagons have smaller angles than planar hexagons and their formation is helped by the decrease in the potential internal bond angle caused by substituents, as suggested by Thorpe and Ingold for small rings. The phenomenon is illustrated with crystal structure data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…On the other hand, according to the literature available, the hydantoins in aqueous solution can be hydrolyzed. In this process, in which ring‐opening occurs to give the ureido acids as intermediate, which can hydrolyze to α‐amino acids (Scheme ),, it was observed that the rate constant increase with increasing pH . It suggests that the second process observed corresponds with the hydrolysis reaction of the 3‐chlorohydantoin formed.…”
Section: Results and Mechanismmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, according to the literature available, the hydantoins in aqueous solution can be hydrolyzed. In this process, in which ring‐opening occurs to give the ureido acids as intermediate, which can hydrolyze to α‐amino acids (Scheme ),, it was observed that the rate constant increase with increasing pH . It suggests that the second process observed corresponds with the hydrolysis reaction of the 3‐chlorohydantoin formed.…”
Section: Results and Mechanismmentioning
confidence: 98%
“…In this process, in which ring-opening occurs to give the ureido acids as intermediate, which can hydrolyze to α-amino acids (Scheme 5), [62,63] , it was observed that the rate constant increase with increasing pH. [64][65][66][67][68] It suggests that the second process observed corresponds with the hydrolysis reaction of the 3-chlorohydantoin formed. The mechanism for this hydrolysis reaction should be analogous to that of the hydantoins proposed in the literature.…”
Section: Hydrolysis Of N-chloro-hydantoins Formedmentioning
confidence: 99%
“…This amine was selected for initial examination as it was expected that cyclization of this substrate would be facilitated by a geminal Thorpe-Ingold effect [17]. The reaction took place in toluene-d 8 at 100 C and was completed in 3.5 h. The reaction work-up was similar to that described for the previous reaction and ( þ )-Moshers acid was used to convert the enantiomers into diastereomers and thus make them detectable for 1 H NMR spectroscopy.…”
Section: Intramolecular Hydroamination Of Aminoalkenesmentioning
confidence: 99%
“…With a planar segment and part of the atoms tetragonal, the sum becomes less than 7208 and partly the conflict is resolved by bond angle opening. We have recently studied [14] the extent of bond angle variation in hydantoins and dihydrouracils with a system four conjugated sp 2 atoms by the analysis of X-ray data from the Cambridge Crystal Structure Database. The average angle at the tetragonal atom of hydantoins (451) is (101.2 AE 1.1)8 while those in dihydrouracils (456 and 561) are (109.9 AE 1.…”
Section: Is 6-oxothiazine 10 An Intermediate In the Elimination Of Ammentioning
confidence: 99%
“…9)8 and (109.7 AE 1.6)8. This served to explain [14] the much stronger gem-dimethyl or dialkyl effect in five-membered rings with planar segments because the Thorpe-Ingold (The gem-dimethyl effect is exhibited in ring stabilization upon substitution in the chain; the Thorpe-Ingold effect refers to the reduction of adjacent bond angles upon substitution favoring small ring stability.) component helps to reduce the bond angles demanded in the formation of the five-membered rings.…”
Section: Is 6-oxothiazine 10 An Intermediate In the Elimination Of Ammentioning
confidence: 99%